Pentingnya Kompetensi Kerja Dalam Meningkatkan Kinerja Pegawai Negeri Sipil di Biro Umum dan Keuangan Universitas Sam Ratulangi Manado - Sumendap, Jefri; Mandey, Jantje; Mambo, Rully (Sam Ratulangi University, 2015)
ABSTRACT : Any public or private organization set up to achieve certain goals, and if achieved then canbe said to be successful. To achieve success, the necessary foundation of competency to be considered,then also increase the performance. Based on strong background in the form of competence. Thus, thecompetence to be very useful to help the organization improve its performance. Competence isindispensable in every process of human resources. The more problems, the study aims to describe theimportance of competence on employee performance.This research uses qualitative research is research that is used to examine the condition of natural objectsin which the researcher is a key instrument. the proper technique to determine the source of the data /informant is